Voluntary Tax Compliance Wajib Pajak Perusahaan Perhotelan: Determinan, Kepercayaan Dan Kekuasaan Legitimasi - Zulkarnain Hakim; Lilik Handajani; Biana Adha Inapty (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2017)
The aim of this research are to give empirical proof about: (1)the influenceprocedural juctice and moral obligation toward voluntary tax compliance. (2) the influenceof trust within mediation influence between procedural juctice and moral obligationtoward voluntary tax compliance. (3) the influence of legitimation power withinmoderation influence of tust toward voluntary tax compliance. Data collection in thisresearch using quisioner. As many as 108 quisioner divided to manager and accountan ineach hotel. From data above, 91 quisioner are given back by responden. So, 91 quisionerscan be used in analysis proses. The result of this research eviden, the procedural jucticeandmoral obligation ralated to voluntary tax compliance. The result of this research alsoeviden the role mediation of trust. Voluntary tax compliance occurs becouse ofprocedural juctice and moral obligation direct to voluntary tax compliance throughmediation of trust, and realionship between trust and voluntary tax compliance are notmoderation by legitimation power.